1996
DOI: 10.1002/j.1460-2075.1996.tb00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of signal sequenceless proteins for export in Escherichia coli with altered protein translocase.

Abstract: Most extracytoplasmic proteins are synthesized with an N‐terminal signal sequence that targets them to the export apparatus. Escherichia coli prlA mutants (altered in the secY gene) are able to export cell envelope proteins lacking any signal sequence. In order to understand how such proteins are targeted for export, we isolated mutations in a signal sequenceless version of alkaline phosphatase that block its export in a prlA mutant. The mutations introduce basic amino acyl residues near the N‐terminus of alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 50 publications
0
59
0
7
Order By: Relevance
“…Presumably because the presence of a signal peptide is necessary but not sufficient to direct protein export, most of the hybrid proteins that we generated remained in the cytoplasm (data not shown). Indeed bona fide presecretory proteins may have a distinctive ability to remain loosely folded that greatly facilitates their export (41). Nevertheless, we found that about 25% of an MBP signal peptide-phosphoglycerate kinase fusion (MBP ss -PGK) was translocated across the IM.…”
Section: Figmentioning
confidence: 84%
“…Presumably because the presence of a signal peptide is necessary but not sufficient to direct protein export, most of the hybrid proteins that we generated remained in the cytoplasm (data not shown). Indeed bona fide presecretory proteins may have a distinctive ability to remain loosely folded that greatly facilitates their export (41). Nevertheless, we found that about 25% of an MBP signal peptide-phosphoglycerate kinase fusion (MBP ss -PGK) was translocated across the IM.…”
Section: Figmentioning
confidence: 84%
“…The SecB/nascent chain interaction has also bcen shown to occur independently of the presence of a signal sequence [5]. Secondl~; translocation of some preproteins in which the signal scquences have been removed strictly requires SecB, even thot, gh they may not be SecB-dependent as a native preprotein [6,7]. The latter is likely a reflection of the targeting flmction of SecB, but again argues against the original kinetic partitioning model in which the retardation of folding by the signal sequence is an important element for recognition.…”
Section: Preprotein Targeting To the Membrane Secb Recognition Sites mentioning
confidence: 99%
“…The so-called pd (for protein localization) class of mutants, which are all isolated as suppressors of signal sequence mutations, have been found in SecA (prlD), SccY (pr/A), SecE (prlG) and more recently in SecG (prlH) (see references in [7,[36][37][38]). It has been proposed that the pr/suppressors function not by restoring the recognition of altered signal sequences but rather by preventing the rejection of defective preproteins from the export pathway [39].…”
Section: Signal Sequence Proofreading At the Initiation Of Translocationmentioning
confidence: 99%
“…In addition, signal sequenceless TreA remained export competent, because it could be exported in prlA4 background (data not shown). prlA mutants are derivatives of secY allowing the export of signal sequenceless secretory proteins (18). To test whether treF could be actively expressed in the periplasm, we fused the signal sequence of TreA to the N terminus of TreF.…”
Section: Resultsmentioning
confidence: 99%